One foot in, one foot out: how does individuals' external search breadth affect innovation outcomes? - Dahlander, Linus; O'Mahony, Siobhan; Gann, David M. (Strategic Management Journal, 2016)
The “variance hypothesis” predicts that external search breadth leads to innovation outcomes, but people have limited attention for search and cultivating breadth consumes attention. How does individuals' search breadth affect innovation outcomes? How does individuals' allocation of attention affect the efficacy of search breadth? We matched survey data with complete patent records, to examine the search behaviors of elite boundary spanners at IBM . Surprisingly, individuals who allocated attention to people inside the firm were more innovative. Individuals with high external search breadth were more innovative only when they allocated more attention to those sources. Our research identifies limits to the “variance hypothesis” and reveals two successful approaches to innovation search: “cosmopolitans” who cultivate and attend to external people and “locals” who draw upon internal people . © 2014 The Authors. Strategic Management Journal published by John Wiley & Sons Ltd.